An Analysis of Illocutionary act in Avengers Infinity War Movie - Riani, Findi (English Language, Linguistics, Literature, And Education Journal, 2022)
This research discusses the illocutionary act in Avengers: Infinity War characters conversation. The aim of this research is to find the kind of illocutionary act and the function of the illocutionary act performs by the character in Avengers: Infinity War movie. The methodology used in this research is descriptive qualitative method. This method requires script and dialogue from the characters in the movie to collect the data then determine the kind of illocutionary act and the function of it based on Searle’s theory. The result of this research is 20 data containing all kinds of illocutionary act which are five data of representative, five data of commissive, five data of directive, four data of expressive, and one data of declarative. The author also found 20 functions of the utterances of five kinds of illocutionary act uttered by the characters in the movie. The most uttered illocutionary acts in the movie are representative, directive, and commisive. The least illocutionary act in the movie is declarative.